Assessment of Forest Fire and Its Impact on Plant Biodiversity of Buffer Zone, Langtang National Park, Nepal - Mamta Bhatta; Rajeev Joshi; Ramesh Prasad Sapkota (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
The research work was focused on the study of forest fire and its impact assessment on plant biodiversity by vegetation assessment in the fire-affected and adjoining non-affected areas to identify the signals of severity and probable causes of fire. Data were collected by quadrate method, site survey, consultation and group discussion, mapping of the studied area, and questionnaire survey. The results show that there was a notable difference in tree and shrub diversity. The Shannon Wienner index (H) = 0.70 and 0.49, and Simpson’s Divesity (D) = 0.64 and 0.51, for trees in adjoining and fire-affected areas respectively. Similarly, Shannon Wienner index (H) = 0.91 and 0.72, and Simpson’s Divesity (D) = 0.84 and 0.68 for shrubs in adjoining and fire-affected areas respectively. Likewise, herb diversity did not differ significantly (H = 1.02 and 0.97; D = 0.87 and 0.88 in the adjacent to burned area and fire-affected area). Gleichenia gigantea, Artemisia dubia, Rubus spp., Oxalis chodata, and some medicinal plants such as Butea minor were found to be most affected by the fire. Mainly dried thickets of Drepanostachyum intermedium and Saccharum spontaneum act as fuel for the fire, which easily ignites and regenerates soon after a fire. Drought before monsoon was found to be the leading cause of forest fires, followed by electricity shooting (17%), ignorance and carelessness (38%), slash and burn practice (15%), other (7%), and unknown causes (23%). Hence the need to better address the drivers of resource extraction from the national park to mitigate this degradation.